Identification by MALDI-TOF MS of Sporothrix brasiliensis isolated from a subconjunctival infiltrative lesion in an immunocompetent patient - Matos, Aline M. F. (2020)
Sporotrichosis is a globally distributed subcutaneous fungal infection caused by dimorphic fungi belonging to the Sporothrix species complex that affects the skin of limbs predominantly, but not exclusively. A rare case of ocular sporotrichosis in an immunocompetent Brazilian patient from the countryside of Rio de Janeiro State is reported. A 68-year-old woman presented with a subconjunctival infiltrative lesion in the right eye with pre-auricular lymphadenopathy of onset 4 months ago that evolved to suppurative nodular lesions on the eyelids. Conjunctival secretion was evaluated by histopathological examination and inoculated on Sabouraud Dextrose Agar (SDA). Histopathology showed oval bodies within giant cells and other mononucleated histiocytes. Fungus grown on SDA was identified as Sporothrix sp. by morphological observations. The isolated strain was finally identified by Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) associated with an in-house database enriched with reference Sporothrix complex spectra. The strain presented a MALDI spectrum with the ion peaks of the molecular mass profile of S. brasiliensis. The patient was adequately treated with amphotericin B subsequently replaced by itraconazole. Due to scars left by the suppurative process, the patient presented poor final visual acuity. The present work presents an overview of ocular sporotrichosis and discusses the diagnostic difficulty that can lead to visual sequelae in these cases.